2021
DOI: 10.1016/s2214-109x(21)00303-x
|View full text |Cite
|
Sign up to set email alerts
|

Vision impairment and traffic safety outcomes in low-income and middle-income countries: a systematic review and meta-analysis

Abstract: Background Road traffic injuries are a major public health concern and their prevention requires concerted efforts. We aimed to systematically analyse the current evidence to establish whether any aspects of vision, and particularly interventions to improve vision function, are associated with traffic safety outcomes in low-income and middle-income countries (LMICs). MethodsWe did a systematic review and meta-analysis to assess the association between poor vision and traffic safety outcomes. We searched MEDLIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…In addition, therapies that mitigate ADHD symptoms translate into more safe driving behavior and accordingly decreased rates of serious crash severity [ 31 ]. Supplementary to this, it has been proved that drivers with poor visual acuity are more prone to road traffic crashes [ 32 ]. Estimated number of crashes contributed to visual field defect has been reported to be 36% higher.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, therapies that mitigate ADHD symptoms translate into more safe driving behavior and accordingly decreased rates of serious crash severity [ 31 ]. Supplementary to this, it has been proved that drivers with poor visual acuity are more prone to road traffic crashes [ 32 ]. Estimated number of crashes contributed to visual field defect has been reported to be 36% higher.…”
Section: Resultsmentioning
confidence: 99%
“…Many accidents occur as a result of loss in visual function. 17 The Centers for Disease Control and Prevention have ranked unintentional injuries (accidents) as the third leading cause of death in the United States (approximately 173,040) per year. 18 Redelmeier and Raza 19 showed that the risk of a life-threatening car accident was highest during the day and was increased by 16% because of the glare induced by bright sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, therapies that mitigate ADHD symptoms translate into more safe driving behavior and accordingly decreased rates of serious crash severity (52,53). Supplementary to this, it is prove that drivers with poor visual acuity are more prone to road tra c crashes (54). A large study on drivers' visual eld in the USA revealed that those suffered from binocular visual eld loss reported two times more crash rates as compared to those without such loss (55).…”
Section: When Dealing With Judiciary Causation Factorsmentioning
confidence: 97%